Social Welfare in the 1990s in Mexico: The Case of "Marginal" Families in the Mazahua Region - Bordi, Ivonne Vizcarra (Anthropologica, 2022)
In Mexico, the official discourse associates social welfare with development opportunities that so- called marginal families are expected to take advantage of. In the Mazahua region, these families commonly are headed by women. To fulfill the official discourse and related bureaucratic demands, the women must fit into organizations and take on new social responsibilities. In this paper, I will examine an initiative from the public sector (PROGRESA) and show that such programs change the household dynamics of families, generating feelings of resentment due to the inclusion/exclusion dynamics involved. Another of the paper’s objectives is to assess how the program’s execution creates new mechanisms of social control.